Analisis Hukum Kebijakan Daftar Negatif Investasi Berdasarkan Peraturan Presiden Nomor 44 Tahun 2016 Terhadap Pengusaha Ritel Indonesia - Nanda Aisyah Rusli; Muhammad Ashri; Nurfaidah Said (Faculty of Law, Andalas University, 2018)
This study aims to determine the implementation of Presidential Regulation No. 44 of 2016 for retailers in Indonesia as well as to know the application of foreign investment in the retail sector in Makassar. This research is an empirical normative research based on library research with regard to the prevailing laws and regulations, legal literature such as books, journals, articles on the internet as well as other legal materials and field studies. The results of this study indicate that given the opportunity for foreign investors to own a maximum of 67% shares, it is considered a policy that causes no restrictions on ownership in the retail industry, so that the attitude of openness is expected to encourage the growth of modern retail expansively. Given the rapidly growing growth of the retail industry, one of the alternative solutions to zoning problems for large-scale modern retailers is required to be in a mall or shopping mall but so far this location permits are not observed by a number of modern retailers Keywords: Foreign Investment, Retail, Modern Retail, Traditional Retail